ADDRESSING BULLYING IN MADAGASCAR’S ELEMENTARY SCHOOLS: PREVENTION AND INTERVENTION STRATEGIES - Eric, Ralainirina Razokiny; Arrive, Jean Tsitaire; Emynorane, Ralaivao Hanginiaina (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This study explores bullying prevention and intervention strategies in five public and private elementary schools in Sakaraha, Madagascar. Using a qualitative descriptive research design, the study employed three data collection methods: observation, semi-structured interviews with teachers and school principals, and documentary analysis of school records and policies. The primary aim was to investigate the prevalence and types of bullying, the awareness of bullying among students and staff, and the effectiveness of current prevention programs. Findings revealed that bullying, particularly verbal and social exclusion, is prevalent during unstructured times such as recess and transitions between classes. While teachers and principals expressed awareness of bullying issues, their responses varied in consistency and effectiveness, with some schools having more active prevention measures than others. School policies on bullying were generally available but lacked detailed, practical guidelines for addressing the issue. Triangulation of data from the three sources confirmed the need for more consistent implementation of anti-bullying practices, clearer communication of policies, and greater student involvement in prevention efforts. The study highlights the importance of a cohesive, school-wide approach to bullying prevention, emphasizing the need for teacher training, student empowerment, and ongoing evaluation of intervention outcomes.